Special Olympics - Hellebuyck, Adam; Deimel, Laura (21st century skills library. Global citizens: sports., 2020)
Examines the history of the Special Olympics, discussing the geography, community, and economics associated with the event. Also explains some of the major rules of the event and what viewers can expect to see. Includes sidebars throughout with critical thinking questions and topics for further research. Also includes color photographs, sources for further information, a glossary, and an index.